Student Engagement Through Creation of New Activities: An Empirical Study on Contributing Student Pedagogy - Maia, Mirna Carelli Oliveira; Araújo, Eliane Cristina; Figueiredo, Jorge; Serey, Dalton (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2020: Anais do XXXI Simpósio Brasileiro de Informática na Educação, 2020)
Contributing Student Pedagogy is an active method that encourages students to contribute to community learning and to value the contributions of others. Activities based on contribution guide students to produce study material and create new exercises for community usage and discuss and evaluate the contribution of others. The creation of new learning exercises can positively influence students' academic performance. This article presents an experimental study to assess how new exercises' creation influences student engagement in programming learning activities. Considering student engagement involves behavior, cognition, and emotion dimensions, this study examined which of these are affected when the student contributes to the community's learning through the production of new programming exercises. Results indicate that the development of this activity improves emotional and cognitive engagement and does not influence behavior. Contributing students reported developing more difficult learning exercises and felt more stimulated, satisfied, and happy. In contrast, those who did not contribute to the community said that their contributions were easier and felt more ashamed and proud.